1976
DOI: 10.1111/j.1365-2184.1976.tb01284.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Colcemid on Mouse Bone Marrow

Abstract: Following Colcemid administration, mitoses accumulate preferentially in the subendosteal region of the bone marrow of the mouse. This finding suggests that the most rapidly proliferating cells are localized to the subendosteal region, and complements previous radioautographic studies which have demonstrated a corresponding labelling gradient in the marrow. Quantitative estimates of cell cycle time by the stathmokinetic method were precluded by the presence of significant Colcemid induced interphase cell loss. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Complementary to the early observations of Weinbeck [18], Shackney and his colleagues labeled bone marrow with tritiated thymidine and found, in histological sections, that the bulk of the proliferative activity was in cells close to bone surfaces [22,23]. This corroborated earlier reports by van Dyke [24,25].…”
Section: Distribution Of Hemopoietic Cellssupporting
confidence: 76%
“…Complementary to the early observations of Weinbeck [18], Shackney and his colleagues labeled bone marrow with tritiated thymidine and found, in histological sections, that the bulk of the proliferative activity was in cells close to bone surfaces [22,23]. This corroborated earlier reports by van Dyke [24,25].…”
Section: Distribution Of Hemopoietic Cellssupporting
confidence: 76%
“…1A). A A fall in marrow cellularity was observed in both Groups I and IV, beginning with the 4-h time point, and reaching a nadir at 24 h. At 24 h marrow cellularity fell to 66% of control values in Group I, and 37% of controls in Group IV, as previously described (1). In Group I, total marrow cellularity retumed to control values by 48 h. In Group IV total marrow cellularity was restored by day four.…”
Section: Resultsmentioning
confidence: 53%
“…In previous studies megakaryocytes were enumerated within an 80 ,um wide sampling band which spanned the marrow section and passed through its center (1,31). While this sampling method was well suited for the enumeration and spatial localization of mitoses and mononuclear cells, it was not ideal for the evaluation of megakaryocytes since the sampling band included only a fraction of the megakaryocytes present in the marrow section (5-7 megakaryocytes per sampling band as compared with 30-50 megakaryocytes per marrow section).…”
Section: Methodsmentioning
confidence: 99%
“…In practical terms, the maximum allowable duration of stathmokinesis is estimated from the linearity of the slope representing cumulative number of mitotic cells in asynchronous populations (14). Whereas in some studies the linear accumulation (or stability) of metaphase cells was observed for up to 8 (15) or even 12 h (8,161, in other reports degeneration of metaphase cells was described after 2.5 or 3 h (12). The subject of instability of cells arrested in mitosis is reviewed by Wright and Appleton (20).…”
mentioning
confidence: 99%